Literasi Keuangan, Kemudahan Pengguanaan, Serta Manfaat Terhadap Penggunaan Quick Response Code Indonesian Standard (QRIS) - Arsanta Iqbal Nugraha; Sri Adji Prabawa (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was conducted with the aim of providing empirical test results regarding the factors that influence the decision to use QRIS in the people of Bengkulu city. The theory used is the technology acceptance model or tam theory as a theoretical reference for research. This type of research is quantitative with probability sampling and simple random sampling techniques using survey or questionnaire methods for 180 respondents. Then the analysis tool used was SmartPLS 4 software. The results of this research found that financial literacy had an influence on the decision to use QRIS among the people of Bengkulu City. Apart from that, the perception of benefits also influences the people of Bengkulu city in deciding to use QRIS as a payment method. Keywords: financial literacy, ease of use, benefits of use, use of QRIS